Nigerian Migrant Women in Confrontation with Trafficking in Persons: The Narrative Agency - Antolinez-Dominguez, Inmaculada; Jorge-Barbuzano, Esperanza (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
For several decades, the arrival of people linked to human trafficking has become important in the analysis of the migration of African population to Spain. Among them, women from Nigeria have a leading role in figures on the phenomenon, mostly for sexual exploitation. One of the fundamental characteristics of Nigerian trafficking is the level of control exercised over the narrative action of women. For this, we have developed a methodology that has sought both to accompany the construction of narratives, such as identify the forms of agency derived from it. The three forms of confrontation of silences and imposed stories detected have had as objectives: the identification as a victim of trafficking and the consequent access to systems of protection; the co-construction of academic knowledge; and protagonist participation in the social dialogue on trafficking.